Unsaid : a novel - Abramson, Neil, 1964- (Center Street, 2011)
After veterinarian Helena Colden dies of breast cancer, she is unable to move on and narrates the emotional deterioration and struggle of her attorney husband David as he becomes involved in a court case to save the life of a chimpanzee.